2017
DOI: 10.4048/jbc.2017.20.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Micropapillary Carcinoma in Axillary Ectopic Breast and Synchronous Ductal Carcinoma In Situ in the Contralateral Breast

Abstract: The development of ectopic breast tissue is attributable to the failure of primitive mammary tissue to regress after the development of the mammary ridge, except at pectoral breast sites, and is most often evident in the axillae. Several benign and malignant breast diseases have been reported in ectopic axillary breast tissues. The most common cancerous pathology of ectopic breast tissue is invasive ductal carcinoma. Ectopic breast cancer presenting with simultaneous primary cancer of the pectoral breast is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…[6][7][8] The most commonly affected region is the axilla, representing 91.5% of the cases. 9 In a review of the literature, it has been reported that 6% of EBT carcinomas occur in male patients. 4 Unlike in our case study, Zhang et al found that EBT carcinoma affects patients at a younger age than BC (72.8% of patients were pre-menopausal).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[6][7][8] The most commonly affected region is the axilla, representing 91.5% of the cases. 9 In a review of the literature, it has been reported that 6% of EBT carcinomas occur in male patients. 4 Unlike in our case study, Zhang et al found that EBT carcinoma affects patients at a younger age than BC (72.8% of patients were pre-menopausal).…”
Section: Discussionmentioning
confidence: 99%
“…4,10 Differentiating an EBT adenocarcinoma from an axillary lymph-node metastasis may be challenging. 4,9 An accurate US and mammographic evaluation, and an adequate tissue sampling are essential to a definitive diagnosis. 9 The presence of normal breast tissue near to the tumor and the presence of immunohistochemical markers usually help the pathologist in achieving the correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This new primary ectopic breast cancer, even with regional nodal metastasis, represents a Stage IIB tumor (Lee et al, 2014, National Comprehensive Cancer Network, n.d.. ; Oh et al, 2017). The respective 5-year survival rates are approximately 20% for Stage IV breast cancer and 40% for Stage IIIB vulvar cancer versus over 90% for Stage IIB breast cancer, highlighting the importance of proper staging and of making this challenging diagnosis (“Cancer Statistics Review, 1975–2014 - SEER Statistics,” n.d.).…”
Section: Discussionmentioning
confidence: 99%